Variation of electrolyte status in relation to the type of acute stroke patients (Bangladesh Medical Journal Khulna, 2020)
Background: Stroke is considered as a major health problem and contributes to serious residual disability and death worldwide. Both serum sodium and potassium disturbance influence negatively on the overall outcome of stroke. There is limited data about electrolyte abnormality in acute stroke, especially from developing countries.Objective: The objective of this study was to evaluate the incidence of electrolyte imbalance in relation to aetiological type of acute stroke patients admitted in hospital.Methods: Total fifty three patients of stroke diagnosed clinically and confirmed by CT scan within 24 hours of onset & consecutively selected for the study after fulfillment of inclusion criteria in the inpatient department of Neuromedicine ward, KhuIna Medical College Hospital from January 2018 to July 2018. Baseline serum electrolytes were estimated along with other biochemical tests as needed. Data were collected and analysed.Results: Fifteen (29%) of ischaemic stroke patients and 4 (8%) of haemorrhagic stroke patients had dyselectrolytaemia. Hyponatraemia was found in 15 (29%) of stroke patients. Hyponatraemia was more common in ischaemic stroke patients (22.6%) than haernorrhagic stroke patients (5.6%). In this study hypokalaernia was found in 3 (5.6%) cases of ischaemic stroke patients and 1 (1.88%) cases of haemorrhagic stroke patients.Conclusion: The incidence of electrolyte disturbance was more in ischaemic stroke than in haemorrhagic stroke and most of which were hyponatraemia followed by hypokalaemia.Bang Med J (Khulna) 2019; 52 : 12-15